Simultaneous EEG-fNIRS study of visual cognitive processing: ERP analysis and decision-related hemodynamic responses in healthy adults. - Tolga Turay; Onur Erdem Korkmaz; Ebru Ergün (PLoS ONE)
This study explores the neural and hemodynamic underpinnings of intentional memory processing through a multimodal approach combining electroencephalography (EEG) and functional near-infrared spectroscopy (fNIRS). Data were drawn from a publicly available dataset in which participants viewed visual scenes and decided whether to remember them, enabling classification into four experimental conditions based on motivation and subsequent memory performance: Want to Remember and Remembered (RR), Want to Remember but Forgot (RF), Did Not Want to Remember but Remembered (FR), and Did Not Want to Remember and Forgot (FF). EEG analyses focused on event-related potentials (ERPs) during the first second following stimulus presentation. The RR and RF conditions showed enhanced ERP amplitudes, particularly in parietal and occipital channels, peaking around 300 ms post-stimulus. Time-frequency analysis using wavelet transform further revealed greater theta and low alpha power in the RR and RF conditions, again especially in parietal and occipital regions. fNIRS analysis examined hemodynamic responses during the subsequent 9-second decision period. While visual inspection revealed variability in oxygenated hemoglobin (HbO) levels across channels and conditions, statistical analyses using Cohen's D and one-way ANOVA did not identify any significant differences between the conditions ([Formula: see text] > 0.05). These findings suggest that while EEG metrics capture early, intention-driven neural dynamics, fNIRS may reflect more distributed and variable patterns of cognitive engagement. The integration of EEG and fNIRS provides a comprehensive framework for investigating cognitive motivation and memory, highlighting the temporal and spatial signatures of intentional memory processing.